PENGARUH DOSIS VAKSIN NEWCASTLE DISEASE INAKTIF PADA ITIK BETINA TERHADAP JUMLAH SEL DARAH PUTIH DAN TITER ANTIBODI - Luthfi Pratama; Purnama Edy Santosa; Siswanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study are determines to: 1) the effect of ND vaccine dose to the number of white blood cells produced in the female ducks; 2) the effect of ND vaccine doses to the amount of antibody titers produced in the female ducks. This research was conducted in December 2015 until January 2016, located in the Sabah Balau, District of Tanjung Bintang, South Lampung regency. Analysis of white blood cells (WBC) conducted in the Central Veterinary of Lampung, while the number of antibody titer was conducted in PT. Vaksindo, Jakarta. The experimental design used in this study is completely randomized design with three replications and 6 treatments (P0: injected 0.5 ml of distilled water, P1: 0.1 ml of ND inactivated vaccine doses, P2: 0.2 ml of ND inactivated vaccine doses, P3: 0.3 ml of ND inactivated vaccine doses, P4: 0.4 ml of ND inactivated vaccine doses, P5: 0.5 ml of ND inactivated vaccine doses). The treatment given to 5 days old female ducks with inactivated ND vaccine.  White blood cells are tested by using the WBC test while antibody titers were tested by using the HI test.  The data result were analyzed by ANOVA at 5% significance level and will be continued by Least Significant Difference (LSD) in white blood cells because the value of analysis of variance showed tangible results. The results of this study showed that giving of inactivated ND vaccine doses significantly (P <0.05) to the number of white blood cells, but did not significantly affect (P> 0.05) titer of antibodies. Keywords: Antibody Titer, Female Ducks, Inactivated ND Vaccine, White Blood Cells